2020
DOI: 10.12997/jla.2020.9.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid Mediators of Myocardial Pathology

Abstract: Cardiomyopathy is the leading cause of mortality worldwide. While the causes of cardiomyopathy continue to be elucidated, current evidence suggests that aberrant bioactive lipid signaling plays a crucial role as a component of cardiac pathophysiology. Sphingolipids have been implicated in the pathophysiology of cardiovascular disease, as they regulate numerous cellular processes that occur in primary and secondary cardiomyopathies. Experimental evidence gathered over the last few decades from both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 212 publications
(244 reference statements)
0
19
0
Order By: Relevance
“…Sphingolipids regulated many cellular processes that occurred in primary and secondary cardiomyopathy, and were also involved in functional categories and pathways, such as “Glycosphingolipid biosynthesis”, “Sphingolipid metabolism” and “sphingolipid metabolic process “. And a large number of studies have shown that disorders of sphingolipid metabolism can cause changes in the structure and function of cardiomyocytes [ 21 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sphingolipids regulated many cellular processes that occurred in primary and secondary cardiomyopathy, and were also involved in functional categories and pathways, such as “Glycosphingolipid biosynthesis”, “Sphingolipid metabolism” and “sphingolipid metabolic process “. And a large number of studies have shown that disorders of sphingolipid metabolism can cause changes in the structure and function of cardiomyocytes [ 21 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that circulating Cer 18:1; O2/24:1, and Cer 18:1; O2/24:0 are associated with the risk of the incidence of major adverse cardiovascular events in healthy people ( 61 ). In the context of cardiomyopathy, increased ceramide levels or changes in ceramide compositions have been suggested to be toxic ( 62 ). The increased levels of SM and Cer were displayed in different type of cardiomyopathies ( 59 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of cardiomyopathy, increased ceramide levels or changes in ceramide compositions have been suggested to be toxic ( 62 ). The increased levels of SM and Cer were displayed in different type of cardiomyopathies ( 59 , 62 ). To date, no sphingolipids studies have been associated with TTS in patient's serum.…”
Section: Discussionmentioning
confidence: 99%
“…Ceramide accumulation was proposed to mediate cardiomyocyte apoptosis induced by ischemia-reperfusion, TNF-α, and palmitate in several rodent models of obesity and diabetes, including the ZDF rats, db/db, and ob/ob mice. 96,156 It has also been shown that cardiomyocyte apoptosis in individuals with obesity and diabetes, as compared to lean individuals, is accompanied by elevated expression of neutral sphingomyelinase and serine palmitoyltransferase, emphasizing the potential role of altered ceramide metabolism in cardiac failure in patients with obesity, with and without T2D (Figure 4). 55 What is the mechanism that underlies these alterations in sphingolipid metabolism?…”
Section: Obesity T2d and Associated Inflammatory Conditionsmentioning
confidence: 98%